The Well-Tempered SIV Infection: Pathogenesis of SIV Infection in Natural Hosts in the Wild, with Emphasis on Virus Transmission and Early Events Post-Infection that May Contribute to Protection from Disease Progression - Raehtz, Kevin (Infect Genet Evol, 2016)
African NHPs are infected by over 40 different simian immunodeficiency viruses. These viruses have coevolved with their hosts for long periods of time and, unlike HIV in humans, infection does not generally lead to disease progression. Chronic viral replication is maintained for the natural lifespan of the host, without loss of overall immune function. Lack of disease progression is not correlated with transmission, as SIV infection is highly prevalent in many African NHP species in the wild. The exact mechanisms by which these natural hosts of SIV avoid disease progression are still unclear, but a number of factors might play a role, including: (i) avoidance of microbial translocation from the gut lumen by preventing or repairing damage to the gut epithelium; (ii) control of immune activation and apoptosis following infection; (iii) establishment of an anti-inflammatory response that resolves chronic inflammation; (iv) maintenance of homeostasis of various immune cell populations, including NK cells, monocytes/macrophages, dendritic cells, Tregs, Th17 T-cells, and γδ T-cells; (v) restriction of CCR5 availability at mucosal sites; (vi) preservation of T-cell function associated with down-regulation of CD4 receptor. Some of these mechanisms might also be involved in protection of natural hosts from mother-to-infant SIV transmission during breastfeeding. The difficulty of performing invasive studies in the wild has prohibited investigation of the exact events surrounding transmission in natural hosts. Increased understanding of the mechanisms of SIV transmission in natural hosts, and of the early events post-transmission which may contribute to avoidance of disease progression, along with better comprehension of the factors involved in protection from SIV breastfeeding transmission in the natural hosts, could prove invaluable for the development of new prevention strategies for HIV.